THE SURGE IDENTIFYING DEVICE IN COMPRESSORS OF AVIATION GAS-TURBINE ENGINES - Olali, N. V.; Olali, M. О. (Science-based technologies, 2019)
This paper concentrates on the problem of identification of surge phenomena in compressors of aviation gas-turbine engines. Applicability of a surge detection method using expansion impulse response of the engine in a series of orthonormal Walsh functions is proved. As a diagnostic sign of a surge the Walsh - Fourier coefficients are accepted. The algorithm and the functional chart of the identification device of a surge are developed. Formation of classes is carried out on the basis of the analysis of a large number of experimental curves of change of parameters in workflow at a surge and normal operation of the engine.